2022
DOI: 10.1093/pnasnexus/pgac226
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fixation pathways across the bacterial and archaeal tree of life

Abstract: Carbon fixation is a critical process for our planet, however, its distribution across the bacterial and archaeal domains of life has not been comprehensively studied. Here, we performed an analysis of 52,515 metagenome-assembled genomes (MAGs) and discover carbon fixation pathways in 1007 bacteria and archaea. We reveal the genomic potential for carbon fixation through the reverse tricarboxylic acid cycle in previously unrecognised archaeal and bacterial phyla (ie. Thermoplasmatota and Elusimicrobiota) and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 79 publications
(78 reference statements)
3
14
0
Order By: Relevance
“…S9). Another Methylophilaceae MAG encoding a complete CBB cycle has been recently reported (63), which supports that the presence of these genes in our host MAGs is not artifactual and that these Methylophilaceae might have the capacity to synthesize 3-phosphoglycerate using various pathways. An interesting point to notice is that, to date, all identified hosts of Absconditicoccaceae epibionts possess RuBisCO (13,14), suggesting that carbon fixation may be advantageous for the establishment of this symbiotic interaction.…”
Section: Resultssupporting
confidence: 86%
“…S9). Another Methylophilaceae MAG encoding a complete CBB cycle has been recently reported (63), which supports that the presence of these genes in our host MAGs is not artifactual and that these Methylophilaceae might have the capacity to synthesize 3-phosphoglycerate using various pathways. An interesting point to notice is that, to date, all identified hosts of Absconditicoccaceae epibionts possess RuBisCO (13,14), suggesting that carbon fixation may be advantageous for the establishment of this symbiotic interaction.…”
Section: Resultssupporting
confidence: 86%
“…The Wood–Ljungdahl pathway (WLP) is one of the seven known pathways for the fixation of carbon dioxide found in nature (Garritano et al, 2022). It is present in strictly anaerobic microorganisms such as methanogenic archaea, sulphate reducing and acetogenic bacteria and catalyses the anabolic formation of acetyl‐CoA from two molecules of CO 2 (Schauder et al, 1988; Wolfe, 1993; Wood et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the 3-hydroxypropionate bi-cycle, discovered in the green non-sulfur bacterium called Chloroflexus aurantiacus [107, 108], has long been considered as an exclusive feature of Chloroflexi. Recent studies, however, have shown that the pathway, or its analogous variants, could exist beyond this single phylum [109, 110]. The present investigation of the Lotus Pond metagenome showed that genes for a few key enzymes of the 3-hydroxypropionate bi-cycle were present in the MAGs affiliated to Aquificae.…”
Section: Discussionmentioning
confidence: 57%